Medication treatment for attention‐deficit/hyperactivity disorder and the risk of acute seizures in individuals with epilepsy. (25th January 2019) - Brikell, Isabell; Chen, Qi; Kuja‐Halkola, Ralf; D'Onofrio, Brian M.; Wiggs, Kelsey K.; Lichtenstein, Paul; Almqvist, Catarina; Quinn, Patrick D.; Chang, Zheng; Larsson, Henrik
Summary: Objective: Attention‐deficit/hyperactivity disorder (ADHD) affects 10%‐30% of individuals with epilepsy, yet concerns remain regarding the safety of ADHD medication in this group. The objective of this study was to examine the risk of acute seizures associated with ADHD medication in individuals with epilepsy. Methods: A total of 21 557 individuals with a seizure history born between 1987 and 2003 were identified from Swedish population registers. Within this study population, we also identified 6773 youth (<19 years of age) who meet criteria for epilepsy, and 1605 youth with continuous antiepileptic drug (AED) treatment. ADHD medication initiation and repeated medication periods were identified from the Swedish Prescribed Drug Register between January 1, 2006 and December 31, 2013. Acute seizures were identified via unplanned visits to hospital or specialist care with a primary seizure discharge diagnosis in the Swedish National Patient Register during the same period. Conditional Poisson regression was used to compare the seizure rate during the 24 weeks before and after initiation of ADHD medication with the rate during the same 48 weeks in the previous year. Cox regression was used to compare the seizure rate during ADHD medication periods with the rate during nonmedication periods. Comparisons were made within‐individual to adjust for unmeasured, time?constant confounding. Results: Among 995 individuals who initiated ADHD medication during follow‐up, within‐individual analyses showed no statistically significant difference in the rate of seizures during the 24 weeks before and after medication initiation, compared to the same period in the previous year. In the full study population 11 754 seizure events occurred during 136 846 person‐years and 1855 individuals had at least one ADHD medication period. ADHD medication periods were associated with a reduced rate of acute seizures (hazard ratio [HR] 0.73, 95% confidence interval [CI] 0.57‐0.94), compared to nonmedication periods within the same individual. Similar associations were found in youth with epilepsy and continuous AED treatment, when adjusting for AEDs, and across sex, age, and comorbid neurodevelopmental disorders. Significance: We found no evidence for an overall increased rate of acute seizures associated with ADHD medication treatment among individuals with epilepsy. These results suggest that epilepsy should not automatically preclude patients from receiving ADHD medications.